Antimicrobial Resistance Genes, Cassettes, and Plasmids Present in Salmonella enterica Associated With United States Food Animals - McMillan, Elizabeth A.; Gupta, Sushim K.; Williams, Laura E.; Jové, Thomas; Hiott, Lari M.; Woodley, Tiffanie A.; Barrett, John B.; Jackson, Charlene R.; Wasilenko, Jamie L.; Simmons, Mustafa; Tillman, Glenn E.; McClelland, Michael; et al. (Frontiers in Microbiology, 2019)
The ability of antimicrobial resistance (AR) to transfer between bacteria on mobile genetic elements (MGEs) can cause the rapid establishment of multidrug resistance (MDR) in bacteria from animals, leading to a foodborne risk to human health. To investigate MDR and its association with plasmids in Salmonella enterica, whole genome sequence (WGS) analysis was performed on 193 S. enterica isolated from U.S. food animals between 1998 and 2011, 119 of which were resistant to at least one antibiotic tested. Isolates represented 86 serovars and variants, as well as diverse phenotypic resistance profiles. A total of 923 AR genes and 212 plasmids were identified among the 193 strains. Every isolate contained at least one AR gene and at least one plasmid was detected in 157 isolates. Genes were identified for resistance to aminoglycosides (n=472), β-lactams (n=84), tetracyclines (n=171), sulfonamides (n=91), phenicols (n=42), trimethoprim (n=8), macrolides (n=5), fosfomycin (n=48), and rifampicin (n=2). The plasmid replicon types detected in the isolates were A/C (n=32), colE (n=76), F (n=43), HI1 (n=4), HI2 (n=20), I1 (n=62), N (n=4), Q (n=7), and X (n=35). Phenotypic resistance correlated with the AR genes identified in 95.4% of cases. Almost all AR genes were located on plasmids, with many of the plasmids encoding multiple AR genes. Thirteen AR genes representing five classes of antibiotics were arranged into six highly conserved cassette-like sequences and one pseudo-cassette (1: sul2, strAB, tetAR; 2: aac3-iid; 3: aph, sph; 4: cmy-2; 5: floR; 6: tetB; pseudo: aadA, aac3-VIa, sul1). These cassettes were present in multiple isolates and on plasmids of multiple replicon types. To determine the current distribution and frequency of these cassettes, the public NCBI database was analyzed, including WGS data on isolates collected by the USDA Food Safety and Inspection Service (FSIS) from 2014 to 2018. Cassette One, Cassette Four, and Cassette Five were significantly associated with cattle isolates while Cassette Six was significantly associated with chicken isolates. This study reveals that a diverse group of plasmids carrying AR genes are responsible for the phenotypic resistance seen in Salmonella isolated from U.S. food animals and many plasmids carry similar AR gene cassettes.